Structure design and optimization of jumping mechanisms based on velocity manipulability - LI Chenjiarui; HOU Yu; SUN Wei; XU Yantao; WANG Zhongxuan (Jixie chuandong)
ObjectiveJumping robots are widely researched in the field of robotics today due to their unique advantages. The structural design of jumping mechanisms is crucial for enhancing the jumping performance of these robots. However, the current jumping mechanisms has the problems of complex structure, poor stability and speed transfer performance.MethodsA single degree of freedom closed-chain six-bar jumping mechanism was designed. The concept of velocity manipulability was introduced as a metric to assess the speed transfer performance of the mechanism, and a particle swarm optimization algorithm was employed for the mechanism optimization.ResultsThe results show that the optimized mechanism exhibits a 21.76% increase in the jumping velocity compared to its pre-optimized state. Additionally, the horizontal jumping distance and vertical jumping height have been enhanced by 48.00% and 48.57% respectively. These validate the rationality of the jumping mechanism design.